2019
DOI: 10.1093/conphys/coy065
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating transport-related stress in endangered Kemp’s ridley sea turtles (Lepidochelys kempii) with a recovery period in saltwater pools

Abstract: Kemp’s ridley sea turtles placed for <6 h in unfamiliar saltwater pools after ground transport exhibited normalization of plasma glucose and potassium, as well as partial improvements in corticosterone and immune measures. A brief period in saltwater pools may help sea turtles recover from transport stress prior to release to sea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
2
13
0
3
Order By: Relevance
“…In prior studies, we confirmed that Kemp’s ridley turtles do experience an adrenal stress response during ground transports of 13 and 26 h duration, with pronounced and significant elevations in plasma corticosterone, plasma glucose, WBC, and H/L ratio immediately post-transport when compared with pre-transport ( Hunt et al. 2016a , 2019 ). Controlled experiments clarified that these changes are primarily due to transportation, with only minor effects attributable to handling, food restriction, or time of day ( Hunt et al.…”
Section: Introductionsupporting
confidence: 81%
See 3 more Smart Citations
“…In prior studies, we confirmed that Kemp’s ridley turtles do experience an adrenal stress response during ground transports of 13 and 26 h duration, with pronounced and significant elevations in plasma corticosterone, plasma glucose, WBC, and H/L ratio immediately post-transport when compared with pre-transport ( Hunt et al. 2016a , 2019 ). Controlled experiments clarified that these changes are primarily due to transportation, with only minor effects attributable to handling, food restriction, or time of day ( Hunt et al.…”
Section: Introductionsupporting
confidence: 81%
“…Therefore, every spring, numerous sea turtles are transported south along the eastern seaboard of the USA in order to release them at beaches with appropriate water temperatures ( Hunt et al. 2016a , 2019 ; NOAA 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…stress, water temperature differences, etc.) ( Stabenau et al , 1991 ; Moon et al , 1999 ; Anderson et al , 2011 ; Innis et al , 2007 , 2008 , 2009 ; Coleman et al , 2016 ; Hunt et al , 2016 , 2019 ). Therefore, extrapolation to wild populations should be done with appropriate caution ( Bolten and Bjorndal, 1992 ).…”
Section: Introductionmentioning
confidence: 99%